2015
DOI: 10.21608/jpp.2015.49564
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Both Soil and Foliar Application of NPK on Response of Corn Varieties in Egypt and Morocco

Abstract: Two field experiments were carried out at Gemiza (ARS), during 2012, 2013. The aim of the study was to evaluate the performance of S.C.167 and T.W.C. 253 maize under the use of different rates of NPK. Fertilizer were tested cross (Cs) , soil application (SA) and foliar one (FA). All the agriculture treatments were used as usual. A split split plot design was used. five traits were studied. Such traits were distributed at ear length, ear diameter, ear height, cob. Weight, and shilling percentage. The obtained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Many investigators documented significant maize hybrids variations regarding growth, yield and its attributed, as Hassaan (2018) who showed that the TWC 352 hybrid had higher number of rows ear -1 and higher grain yield in both seasons compared with the other tested hybrids. El-Hassanin et al (2015), Awadalla and Morsy (2016), Eyasu et al (2018), Ali andAbdelaal (2020), Casimir et al (2020) and Yasser et al (2020) found similar results.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Many investigators documented significant maize hybrids variations regarding growth, yield and its attributed, as Hassaan (2018) who showed that the TWC 352 hybrid had higher number of rows ear -1 and higher grain yield in both seasons compared with the other tested hybrids. El-Hassanin et al (2015), Awadalla and Morsy (2016), Eyasu et al (2018), Ali andAbdelaal (2020), Casimir et al (2020) and Yasser et al (2020) found similar results.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, it is essential to test the other methods to provide the necessary nutrients for productivity of the crop while keeping soil structure in great shape and environmentally clean (Miransari, 2011). Soil application of 100% mineral NPK gave the highest production on all studied traits (El-Hassanin et al, 2015). Nano-fertilizers offer an opportunity for efficiently improving plant mineral nutrition, increase food production whilst simultaneously reducing adverse environmental impacts.…”
Section: Introductionmentioning
confidence: 99%